Forest geopolitics in Central Africa - (:unkn) unknown (My University, 2020)
In contrast to other regions of the world, Africa could soon become the continent of deforestation, with DRC losing more than 1 million ha of tree cover per year. In Central Africa, small-scale agriculture is the main driver of deforestation. Its expansion is associated with demographic patterns and the desire to build up a land heritage. Land grabbing of forestland by agribusiness remains limited, as most of the impressive announcements have turned out to be short-lived due to local people resistance and government reluctance. Forest exploitation is still mostly carried out under the concession regime, but European interests have become a minority in the face of Asian conglomerates, particularly Chinese. The emergence of Sino-Indian rivalry in the forestry sector is emerging in Gabon. Successive international initiatives have not achieved convincing results, and the REDD+ process remains essentially a showcase for donors with no real grip on the ground. Gabon has been able to take advantage of a skillful climate diplomacy that gives it a leadership previously holdby the DRC. The 2020 crisis could reduce some pressures on forests (infrastructure and extractive activities), but may increase others, as many neo-unemployed people will have to resort to subsistence farming.
Keywords: African Research